A Study of Credit Rating Potential and Awareness Among SMEs in Baddi Region of Himachal Pradesh - Bedi, Sarbjit Singh; Lal, Amit Kumar; Kaur, Sukhwinder (Prabandhan: Indian Journal of Management, 2013)
Purpose: This research paper aims to find out the awareness level of credit-rating agencies among SMEs and to find out the factors which enhance the growth of credit rating products. Design/Methodology/Approach: Data was collected through self administered survey of around 150 SMEs in Baddi, Una and Panchkula region, and exploratory factor analysis was conducted to analyze the data with the help of SPSS 16.0. Findings: The findings reported that most of the SMEs lacked awareness about Credit rating products. The three factors which can enhance the effectiveness of credit rating companies are managerial effectiveness, credibility and creative marketing efforts. Originality/Value: This paper provides an empirical evidence of SMEs awareness about credit rating products. This paper also suggests why SMEs are lacking opportunities of getting benefits of Credit rating products.